2022
DOI: 10.1093/mr/roac013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of large-vessel giant cell arteritis in Japanese patients: A single-centre retrospective cohort study

Abstract: Objectives Recent advances in imaging revealed that giant cell arteritis (GCA) is frequently associated with large vessel involvement (LVI), but they may also contribute to earlier diagnosis and treatment of LV-GCA. We aimed to compare clinical characteristics of GCA with or without LVI and evaluate its association with clinical outcomes. Method We retrospectively reviewed the medical records of 36 patients with GCA in Kyoto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…A retrospective study from Japan found that 18 out of 36 (50%) patients had involvement of non-cranial arteries (33), while another retrospective study from New Zealand found documented involvement of non-cranial arteries in only 10 out of 142 (7%) patients (29).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A retrospective study from Japan found that 18 out of 36 (50%) patients had involvement of non-cranial arteries (33), while another retrospective study from New Zealand found documented involvement of non-cranial arteries in only 10 out of 142 (7%) patients (29).…”
Section: Discussionmentioning
confidence: 98%
“…A major difference between these studies and our study is the study design, with the possibility of missing imaging data for some patients in our study causing a possible underestimation of non-cranial involvement. A retrospective study from Japan found that 18 out of 36 (50%) patients had involvement of non-cranial arteries ( 33 ), while another retrospective study from New Zealand found documented involvement of non-cranial arteries in only 10 out of 142 (7%) patients ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kermani et al [ 4 ] showed that among patients with GCA, aortic manifestations were associated with increased mortality. On the other hand, Yamaguchi E. et al reported that GCA without LVI has more active disease, more vascular damage, and worse survival than LV-GCA [ 32 ]. Our cohort’s overall survival of Japanese patients with GCA was favorable, and LVI was not associated with relapse or survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study showed no significant difference between patients with and without LVI. Recently, another cohort study of Japanese GCA patients reported no difference in age or prevalence of PMR with or without LVI [ 32 ]. Our study was consistent with the previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Large vessel involvement can be complicated by aortic dissection and aneurysm formation, while inflammation of medium-sized arteries causes headache, jaw claudication, loss of vision, and stroke. Moreover, extravascular manifestations —such as fever, malaise, weight loss, polymyalgia rheumatica—also frequently occur ( Buttgereit et al, 2016 ; Yamaguchi et al, 2022 ). The currently available treatments for GCA include glucocorticoids and tocilizumab (TCZ), an IL-6 receptor inhibitor.…”
Section: Introductionmentioning
confidence: 99%